Beyond the Suffering of Being: Desire in Giacomo Leopardi and Samuel Beckett - Cauchi-Santoro, Roberta (Studi e saggi, 2016)
This book challenges critical approaches that argue for Giacomo Leopardi's and Samuel Beckett's pessimism and nihilism. Such approaches stem from the quotation of Leopardi in Beckett's monograph Proust, as part of a discussion about the removal of desire. Nonetheless, in contrast to ataraxia as a form of ablation of desire, the desire of and for the Other is here presented as central in the two authors' oeuvres. Desire in Leopardi and Beckett is read as lying at the cusp between the theories of Jacques Lacan and Emmanuel Levinas, a desire that splits as much as it moulds the subject when called to address the Other (inspiring what Levinas terms 'infinity' as opposed to 'totality,' an infinity pitted against the nothingness crucial to pessimist and nihilist readings).